Additive Effects of Environmental Enrichment and Ketamine on Neuropathic Pain Relief by Reducing Glutamatergic Activation in Spinal Cord Injury in Rats - Tai, W. L.; Sun, L.; Li, H.; Gu, P.; Joosten, E. A.; Cheung, C. W. (Frontiers in Neuroscience, 2021)
Spinal cord injury (SCI) impairs mobility and often results in complications like intractable neuropathic pain. An multi-approach management of this chronic pain condition has been encouraged but little has been explored of the field. Here, we focus on the effect and underlying mechanism of Environmental enrichment (EE), which promotes voluntary social and physical activities, combined with a clinical analgesic, ketamine, on SCI-induced neuropathic pain as well as motor dysfunction. We performed T13 spinal hemisection in rats, which induced unilateral motor impairment and neuropathic pain-like behaviors in the hindlimb. Treatment regimen started a week after SCI, which consists of ketamine administration (30 mg kg-1 day-1; intramuscular) for 10 days, or EE housing for 20 days, or their combination. Paw withdrawal response to mechanical and thermal stimuli, motor function, burrowing behaviors, and body weight were monitored. Spinal segments at T13 lesion and L4-6 were collected for histopathological and protein analysis. The joint treatment of EE and ketamine provided greater relief of pain-like behaviors and locomotor recovery compared to either paradigm alone. These improvements were associated with reduced cavitation area, astrogliosis, and perilesional phosphorylation of glutamate N-methyl-D-aspartate receptor (NMDAR). Concurrently, lumbar spinal analysis of NMDAR-linked excitatory markers in hypersensitization showed reduced activation of NMDAR, mitogen-activated protein kinase (MAPK) family, nuclear factor (NF)-κB, interleukin (IL)-1β signaling, and restored excitatory amino-acid transporter 2 level. Our data supports a better therapeutic efficacy of the combination, EE and ketamine, in attenuation of neuropathic pain and motor recovery by reducing spinal glutamatergic activation, signifying a potential multifaceted neurorehabilitation strategy to improve SCI patient outcome.